2011
DOI: 10.1149/1.3599832
|View full text |Cite
|
Sign up to set email alerts
|

Chemical States of Copper Contaminants on SiO2 Surfaces and Their Removal by ppm-order HCN Aqueous Solutions

Abstract: Cu contaminants of $1 Â 10 13 atoms/cm 2 on SiO 2 surfaces can be removed to less than $3 Â 10 9 atoms/cm 2 by immersion in 3 ppm HCN aqueous solutions within 2 min at room temperature. The Cu removal process by HCN aqueous solutions consists of the initial fast and subsequent slow steps. X-ray absorption fine structure (XAFS) measurements with the total reflection X-ray fluorescence (TXRF) geometry (TXRF-XAFS) have been used for determination of chemical states of Cu contaminants before and after cleaning wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…In our previous paper, we have found that ammonium hydroxide aqueous solutions cannot remove Cu contaminants below 10 11 atoms/cm 2 , but addition of low concentration (e.g., 2.7 ppm) HCN in the solutions can remove Cu to the concentration below ∼3 × 10 9 atoms/cm 2 . 20 Fig. 3 shows changes in the minority carrier lifetime of the assliced Si wafers.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous paper, we have found that ammonium hydroxide aqueous solutions cannot remove Cu contaminants below 10 11 atoms/cm 2 , but addition of low concentration (e.g., 2.7 ppm) HCN in the solutions can remove Cu to the concentration below ∼3 × 10 9 atoms/cm 2 . 20 Fig. 3 shows changes in the minority carrier lifetime of the assliced Si wafers.…”
Section: Resultsmentioning
confidence: 99%
“…We have already reported that HCN solutions possess high activity for metal removal, which activity enables cleaning with ultra-low concentration solutions at room temperature. [6][7][8][9][10] Since metal species removed from surfaces are present in the form of metal-cyanide complex ions (e.g., Cu(CN) 4 3− ) which are extremely stable in aqueous solutions, 11 re-adsorption of the removed metals does not proceed, which makes it possible to use the cleaning solutions repeatedly. Avoidance of re-adsorption also enables to remove metal contaminants to extremely low levels.…”
Section: Discussionmentioning
confidence: 99%
“…6-10 CN − ions possess high metal removal activity resulting from formation of metal-cyanide complex ions, 11 and therefore, cleaning can be performed using ultra-low concentration HCN solutions at room temperature. 10 Due to high stability of metal-cyanide complex ions in the cleaning solutions, re-adsorption is completely prevented, and thus, metal contaminants can be removed completely even when HCN solutions are used repeatedly for cleaning. Moreover, CN − ions are selectively adsorbed on defect states such as Si dangling bonds, resulting in defect passivation, and thus improving conversion efficiency of Si solar cells.…”
mentioning
confidence: 99%